Levodopa Responsive Parkinsonism in Patients with Hemochromatosis: Case Presentation and Literature Review - Tarun Girotra; Abhimanyu Mahajan; Christos Sidiropoulos (Case Reports in Neurological Medicine)
Hemochromatosis is an autosomal recessive disorder which leads to abnormal iron deposition in the parenchyma of multiple organs causing tissue damage. Accumulation of iron in the brain has been postulated to be associated with several neurodegenerative diseases including Parkinson’s disease. The excess iron promotes Parkin and α-synuclein aggregation in the neurons. Excess iron has also been noted in substantia nigra on MRI especially using susceptibility weighted imaging in patients with Parkinson’s disease. We present a case of a young male with alleles for both C282Y and H63D who presented with signs of Parkinsonism and demonstrated significant improvement with levodopa treatment.